Analysis of Health Drinks : What is Satisfying Consumer's Thirst ? - Bhagat, Shikha; Ravi, Shilpa Sarvani (Indian Journal of Marketing, 2018)
The ever - raising dynamics in the Indian market place and the extensive competition has emphasized on the significance in identification of factors behind the consumers' consumption of health drinks to quench the thirst of the marketers with solutions. This study identified 32 different underlying reasons as factors for a consumer to prefer health drinks. The study analyzed survey responses of 432 respondents from South Bengaluru. Furthermore, the study examined the significance of each factor with its impact on purchase intentions of health drinks using exploratory factor analysis. The interpretation was then carried out to analyze how each factor - Advertisement, Support-Drink, Influence, Lifestyle, Relaxation, Activeness, Arousal, Health-Consciousness, Taste, Price, and Packaging impacted the purchase intentions. The results of the regression analysis further revealed that Activeness, Relaxation, Packaging, Arousal, Advertisement, Health - Consciousness, and Taste had a significant impact on consumer purchase intentions about health drinks. The study revealed that 'Activeness' was the utmost preferred attribute for the preference of health drinks by the consumers.